Renewable Energy as a Driver of Grid Resilience: Evidence and Policy Implications - Biancardi, Alberto; D’Adamo, Idiano; Gastaldi, Massimo; Ierfone, Francesco Pio (International Journal of Energy Economics and Policy, 2026)
The increasing penetration of renewable energy sources into power systems makes new grid infrastructure upgrades and more accurate tools for assessing their economic sustainability essential. In this framework, this study examines the economic and financial feasibility of the Sardinia–Corsica–Italy 3 interconnection project using the advanced cost-benefit analysis model (CBA 2.0). The results indicate strong economic convenience: the net present value (NPV) reaches 2110 million €, while the discounted benefit-cost ratio (DBCR) stands at 3.41. The main advantages stem from improved socio-economic welfare and a greater capacity to integrate renewable energy; additional benefits include reduced risks related to energy supply, increased grid resilience, and more efficient management of the Sardinian power system. Sensitivity analyses confirm the robustness of these outcomes, with NPVs ranging between 1977 and 2248 million € and DBCR values between 3.12 and 3.77, variations primarily driven by the discount rate and capital expenditure. The study thus highlights how the central role of renewable energy and grid resilience, combined with advanced CBA methodologies, can support investment decisions consistent with energy transition goals.